Development of Media Sound Slide in Learning Literation Read-Write for 2nd Grade Elementary School - Helyu Tsuro'iyah; Ratih Asmarani; Bambang Yulianto (Universitas Muhammadiyah Enrekang, 2020)
Reading is an important part of the learning process to explore information both of in writing or orally. Thus the basic literacy that is often applied is read-write literation. This study aims to develop sound slide media in learning literacy for second grade of elementary school. To knowing how the process of media development and how the quality of the media. This research is a type of research and development with a 4-D model oriented from S. Thiagarajan, et al. This 4-D development is modifed by reserchers in accordance with research needs, namely the define, design and develop stages without dissimante. The research subject were grade 2 students of elementary school in 2019/2020. Based on field trials the revised validity assesment results occupy a valid category with an overall average of 83,45. Then the learning outcomes of student with an everage of 86, the students completed with a percentage of 90% or 9 people and the percentage 10% or 1 person who did not complete.